Photocatalytic decolorization of azo dyes on TiO2: Prediction of mechanism via conceptual DFT - Turkten, Nazli; Cinar, Zekiye (ELSEVIER, 2017)
The aim of this study is to develop a shortcut method to predict the intermediates and the mechanism of decolorization reactions of azo dyes. To this purpose, Reactive Red 195 (RR195) was chosen as the representative member of azo dyes and photocatalytic decolorization reaction of RR195 in the presence of TiO2 under UV-A light irradiation was investigated. TiO2 was synthesized by an acid-catalyzed sol-gel method from an alkoxide precursor and characterized by XRD, XPS, ESEM-EDX and BET measurements. The decolorization reaction was monitored by UV-vis, FTIR, GC-MS and ESEM-EDX techniques. Conceptual Density Functional Theory was applied to the degradation reaction of the target molecule and reactivity descriptors were calculated by means of DFT/B3LYP/6-31G* level of theory. Eventually, the reactive sites of the molecule for center dot OH radical attack were determined and the reaction mechanism was predicted by combining the results of the DFT calculations with the experimental FTIR and GC-MS analyses. The predicted mechanism was confirmed by comparison with the experimental results on simple structures reported in the literature. The results of the study suggest that TiO2/UV photocatalysis may be used as a method for treatment of diluted wastewaters in textile industries, adsorption on TiO2 surface occurs through sulfo and carbonyl groups of the dye molecule, while decolorization by the breaking of the -N=N- double bond of the chromophore group. (C) 2017 Published by Elsevier B.V.
Keywords: TiO2 nanoparticles; Photocatalysis; Reactive Red 195; Conceptual Density Functional Theory; DFT reactivity descriptors; SYNTHETIC ORGANIC-DYES; DEGRADATION; WASTEWATERS; REMOVAL; DECONTAMINATION; ADSORPTION; OXIDATION; PATHWAYS; SURFACE; Chemistry; Engineering